Simple bit loading algorithm for OFDM-based systems - Nader-Esfahani, S.; Afrasiabi, M. (IET communications, 2007)
A simple and efficient bit loading algorithm for orthogonal frequency division multiplex-based systems in frequency selective environments is presented in this study. The proposed algorithm minimises the total transmitted power for a given bit rate and probability of error. Simulation results show that the proposed algorithm has approximately the same performance as the optimal algorithms with much less complexity. When compared with suboptimal algorithms, computational complexity is comparable while the overall performance is much closer to the optimum solution.